FAKTOR DOMESTIK DALAM KEBIJAKAN PEMERINTAH HUNGARIA TERHADAP PENGUNGSI DAN MIGRAN DARI TIMUR TENGAH PERIODE TAHUN 2015-2019 - Angga Nurdin Rachmat (Jurnal Academia Praja, 2021)
Hungary has become a party to the 1951 Convention and 1967 Protocol on Refugees which requires it to adhere to the principle of non-refoulment towards refugees and migrants from the Middle East who came to the country in 2015. However, in reality Hungary has implemented a policy of detaining and returning refugees even by repressive means. This policy also clearly contradicts the principle of protection against refugees and the policies of the European Union (EU) in which Hungary is a member. The policies taken by Hungary cannot be separated from domestic factors that influence the choice of the Hungarian government to take policies that are contrary to the binding Convention and EU policy. Therefore, this paper seeks to answer what domestic factors influenced Hungary's policies towards refugees and migrants from the Middle East in the 2015-2019 period. This paper uses qualitative methods with data sources obtained from literature studies on various aspects of Hungarian domestic politics. The argument in this study is that Hungarian policy towards refugees and migrants is influenced by domestic factors related to elite interests as a strategy to win political battles in the country related to Viktor Orban's ideas of national identity as the Prime Minister of Hungary as well as leader of the ruling party Fidesz, the dynamics of Hungarian domestic politics. and the strengthening of right-wing populism advocated by Fidesz's party.